RATIONALE BEHIND USING KAHOOT IN FOREIGN LANGUAGE CLASSES IN MODERN HIGHER EDUCATION INSTITUTIONS: EMPIRICAL ASPECT - Fursenko, Тетяна; Druz, Юрій; Druz, Галина (Journal of Information Technologies in Education (ITE), 2024)
Annotation. Methodology of language teaching has been in constant search for effective strategies, approaches and tools to facilitate students` progress in mastering a foreign language. Due to digitalization in education and society, a huge focus is now placed on ICT as a powerful instrument for boosting students` skills and knowledge. The article aims to experimentally verify the effectiveness of using Kahoot in ESP class for students majoring in Information Technologies in academic settings. The objectives of the current research are twofold. Primarily, the research is the attempt to measure and evaluate the influence of Kahoot on students` vocabulary comprehension as compared to traditional paper-based activities (multiple choice tests, filling-in-the-gaps activities etc.). Secondly, our goal is to assess students` attitude to the technology and the effect it has on their motivation. To accomplish the outlined objectives we have conducted a pedagogical experiment among 27 students based on qualitative (a questionnaire, vocabulary tests) to gather data and quantitative methods (Student`s t test, math proportions and equations) to process the obtained results and prove their validity by excluding the possibility of all the findings being a random coincidence. All the experiment participants consented to taking part in the research. Having carried out the experiment, we indicated a difference of around 20 % in the performance given by the experimental group in the vocabulary test as compared to the control group. Thus, we can reach a conclusion that the introduction of Kahoot in the process of studying English at university has proved to be effective and there is a rationale behind incorporation the studied tool in the learning process on a regular basis. As for assessing the students` motivation, the questionnaire results have shown that the experimental group students give a positive feedback on using Kahoot, pointing out a few aspects they spot to be problematic (narrow time limit, screen brightness). However, all such drawbacks can be easily customized and troubleshot. Possible areas that can be of interest for further reach can be using Kahoot for other aspects of language learning (grammar, listening comprehension).